Grain growth stagnation in thin films due to shear-coupled grain boundary migration. (15th April 2020) - Rabkin, Eugen; Srolovitz, David J.
Abstract: Normal grain growth in thin films attached to a substrate has been considered. It has been shown that shear-coupled grain boundary migration results in the build-up of elastic stresses in the film. A semi-quantitative model of grain growth combining the elements of disclinations theory with the Burke-Turnbull model of normal grain growth has been proposed. It has been shown that shear-coupled grain boundary migration may lead to stagnation of normal grain growth, whereas for high coupling factor values, the grains in the film do not grow at all. Finally, the mechanisms of stress relaxation enabling some grain growth are discussed. Graphical abstract: Image, graphical abstract